Knowee
Questions
Features
Study Tools

Given grammar G:S->aS| ABA-> eB-> eD-> bReduce the grammar, removing all the e productions:

Question

Given grammar G:

S -> aS | A
A -> e
B -> e
D -> b

Reduce the grammar, removing all the e productions:

🧐 Not the exact question you are looking for?Go ask a question

Solution

The given grammar is:

G: S -> aS | ABA
A -> e
B -> e
D -> b

The first step in removing the e productions (also known as epsilon productions) is to identify the nullable variables. A nullable variable is a variable that can generate the empty string. In this case, A and B are nullable variables because they both produce e.

Next, we need to modify the grammar by removing the e productions and adding new productions for each combination of nullable variables in the right-hand side of the original productions.

The modified grammar is:

G: S -> aS | aA | aB | a | ABA | AB | AA | A | BA | B | A | 
A -> 
B -> 
D -> b

In the new grammar, we have removed the e productions and added new productions for each combination of nullable variables in the right-hand side of the original productions. For example, the original production S -> aS has been replaced with four new productions: S -> aS, S -> aA, S -> aB, and S -> a. This is because S could be replaced with any combination of A and B, which are both nullable variables.

Finally, we remove any productions that have become useless. In this case, the productions A -> and B -> are useless because they do not produce any terminals, so we can remove them. The final grammar is:

G: S -> aS | aA | aB | a | ABA | AB | AA | A | BA | B | A | 
D -> b

This problem has been solved

Similar Questions

Given grammar G:S->aS| ABA-> eB-> eD-> bReduce the grammar, removing all the e productions:

For the given Context free grammar reduce the following grammar SaBDh A Bbc | b DdD

Reduce the grammar to Chomsky normal formS→ ABAC | aCAA→ aA | εB→ bB | εC→ dD→ f

Use the string “ababab” to show that the following grammar is ambiguous: 𝑆 → 𝑆𝑆 | 𝑇 𝑇 → 𝑎𝑇𝑏 | 𝑎𝑏

Suppose A → xBz and B → y, then the simplified grammar would be:Select one:a. None of the mentionedb. A → xBz|xyzc. A → xyz d. A → xBz|B|y

1/1

Upgrade your grade with Knowee

Get personalized homework help. Review tough concepts in more detail, or go deeper into your topic by exploring other relevant questions.